New Pyrazolo-Benzimidazole Mannich Bases with Antimicrobial and Antibiofilm Activities - Christina Zalaru; Florea Dumitrascu; Constantin Draghici; Isabela Tarcomnicu; Maria Marinescu; George Mihai Nitulescu; Rodica Tatia; Lucia Moldovan; Marcela Popa; Mariana Carmen Chifiriuc (MDPI AG, 2022)
A new series of pyrazolo-benzimidazole hybrid Mannich bases were synthesized, characterized by 1H-NMR, 13C-NMR, IR, UV-Vis, MS, and elemental analysis. In vitro cytotoxicity of the new compounds studied on fibroblast cells showed that the newly synthesized pyrazolo-benzimidazole hybrid derivatives were noncytotoxic until the concentration of 1 μM and two compounds presented a high degree of biocompatibility. The antibacterial and antibiofilm activity of the newly synthesized compounds was assayed on Gram-positive Staphylococcus aureus ATCC25923, Enterococcus faecalis ATCC29212, and Gram-negative Pseudomonas aeruginosa ATCC27853, Escherichia coli ATCC25922 strains. All synthesized compounds 5a-g are more active against all three tested bacterial strains Staphylococcus aureus ATCC25923, Enterococcus faecalis ATCC29212, and Escherichia coli ATCC25922 than reference drugs (Metronidazole, Nitrofurantoin), with the exception of compounds 5d and 5g, which are less active compared to Nitrofurantoin, and all synthesized compounds 5a-g are more active against Pseudomonas aeruginosa ATCC27853 compared to reference drugs (Metronidazole, Nitrofurantoin). Compound 5f showed the best activity against Staphylococcus aureus ATCC 25923, with a MIC of 150 μg/mL and has also inhibited the biofilm formed by all the bacterial strains, having an MBIC of 310 µg/mL compared to the reference drugs (Metronidazole, Nitrofurantoin).